The Effect of STEAM on Science Learning on Student Learning Achievement: A Meta-Analysis - Asrizal Asrizal; Muhammad Dhanil; Usmeldi Usmeldi (Postgraduate, University of Mataram, 2023)
STEAM is a popular approach used in learning by integrating several fields of science in the form of science, technology, engineering, art, and mathematics. This study aims to determine the effect of size from studies that discuss the effect of STEAM on science learning on learning achievement. The moderator variable consists of the level of education and the distribution of regions. This research is a meta-analysis study by collecting quantitative data to calculate the effect size of each study. Studies were collected through national and international journal research using Google Scholar and ERIC in the range of 2012 to 2022. The effect of STEAM on science learning on student learning achievement had an average size effect score of 0.71 in the moderate category obtained from 20 studies. The distribution of studies discussing STEAM is most commonly found in the South Korean region. The influence of STEAM varies on the level of education dominated in elementary schools.